2005
DOI: 10.1111/j.1365-2893.2005.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution, virologic and clinical characteristics of hepatitis B virus genotypes in China

Abstract: The significance of hepatitis B virus (HBV) genotypes for the heterogeneity of chronic HBV infection and severity of liver disease is not well understood. The aim of this study was to determine the distribution and virologic characteristics of HBV genotypes in China and possible association with the diversity of liver disease. The study includes 1096 chronic HBV carriers from nine provinces in China. We collected clinical and laboratory data and analysed the HBV strains in sera by polymerase chain reaction-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
100
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 32 publications
13
100
0
Order By: Relevance
“…Fundamental questions regarding the fluctuating nature of the disease (22), the not-yet-fully understood mechanism behind HBV flare-ups after stress conditions and immunosuppression (23), and the reason for the geographical diversity and the much more aggressive course of the disease in certain countries (24), could be now approached from a different point of view. Keeping in mind that in terms of regulation and response to nutritional stimuli, HBV is very similar to metabolic genes, one can attribute certain dynamic changes in the natural Forty-eight hours later, mice were divided into two groups: a control group (n ϭ 5) that was allowed continuous free feeding and an experimental group (n ϭ 8) that was subjected to a 7-h fast and to a subsequent 12-h refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental questions regarding the fluctuating nature of the disease (22), the not-yet-fully understood mechanism behind HBV flare-ups after stress conditions and immunosuppression (23), and the reason for the geographical diversity and the much more aggressive course of the disease in certain countries (24), could be now approached from a different point of view. Keeping in mind that in terms of regulation and response to nutritional stimuli, HBV is very similar to metabolic genes, one can attribute certain dynamic changes in the natural Forty-eight hours later, mice were divided into two groups: a control group (n ϭ 5) that was allowed continuous free feeding and an experimental group (n ϭ 8) that was subjected to a 7-h fast and to a subsequent 12-h refeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of genotype B without recombination are found in Japan (subgenotype B1), whereas strains with recombination between genotype B and C are found throughout Asia (subgenotype B2), sparing Japan [67] . Recombinants between HBV genotypes C and D are the leading HBV subgenotype in Tibet [68][69][70] . It remains open for discussion whether the observed exchang es are the consequence of direct g enetic recombination taking place between two HBV strains or if they are the consequence of fast adaptation of HBV to a certain genetic and immunologic environment in different human populations in the world.…”
Section: Figurementioning
confidence: 99%
“…Studies evaluating an association between the rate of HBeAg or HBeAb positivity and genotypes B and C have shown conflicting results. 11,16,21 The present study demonstrated that patients infected with HBV genotype B had significantly lower HBeAg and significantly higher HBeAb positivity rates compared with those infected with genotype C. This could be attributed to earlier HBeAg seroconversion following infection with HBV genotype B than with HBV genotype C infection. 22 Mutations in the basal core promoter region which can affect the expression of HBeAg should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 50%
“…The present study demonstrated that genotypes B (57.9%), C (16.0%) and BC (26.1%) exist among the two nationalities (Tibetan and Han) in the Sichuan Province of China, which supports the view that the infection ratio of genotype B gradually rises from the north to the south of China. 16 The prevalence of the three genotypes in Tibetan and Han nationals was significantly different (P < 0.05), with the most prominent difference being the significantly high prevalence (62.2%) of the mixed genotype BC among Tibetan nationals compared with the Han population from the same area. This difference seems to be nationality related.…”
Section: Discussionmentioning
confidence: 99%